2002
DOI: 10.1021/jf011541q
|View full text |Cite
|
Sign up to set email alerts
|

Essential Oil Constituents and in Vitro Antimicrobial Activity of Decalepis hamiltonii Roots against Foodborne Pathogens

Abstract: Hydrodistillation of Decalepis hamiltonii roots yielded an essential oil (0.33% v/w) that contained 2-hydroxy-4-methoxybenzaldehyde (37.45%), 2-hydroxybenzaldehyde (31.01%), 4-O-methylresorcylaldehyde (9.12%), benzyl alcohol (3.16%), and alpha-atlantone (2.06%) as major constituents, with aromatic aldehydes constituting the main fraction of this root's essential oil. The oil was tested for its antimicrobial activity against foodborne pathogens responsible for food spoilage and human pathologies using standard … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
25
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(31 citation statements)
references
References 5 publications
5
25
0
1
Order By: Relevance
“…Methanol extract of A. procera showed antifungal activity against seven fungal strains and ethyl acetate extracts showed activity against any five fungi [11] In addition these results confirmed the evidence in previous studies reported that the methanol is a better solvent for more constituent extraction of antimicrobial substance from medicinal plants compared to other solvents such as water, ethanol and hexane [12,[13][14]. The antimicrobial activity of D. hamiltonii against human pathogenic bacteria and food borne fungi has been demonstrated by [15] …”
Section: Discussionsupporting
confidence: 78%
“…Methanol extract of A. procera showed antifungal activity against seven fungal strains and ethyl acetate extracts showed activity against any five fungi [11] In addition these results confirmed the evidence in previous studies reported that the methanol is a better solvent for more constituent extraction of antimicrobial substance from medicinal plants compared to other solvents such as water, ethanol and hexane [12,[13][14]. The antimicrobial activity of D. hamiltonii against human pathogenic bacteria and food borne fungi has been demonstrated by [15] …”
Section: Discussionsupporting
confidence: 78%
“…'utilisation des substances naturelles a Ia place des composes synthetiques a fait promouvoir des etudes plus approfondies pour ! 'exploitation des ressources des plantes (Thangadurai et a/., 2002). Les plantes superieures et leurs huiles essentielles utilisees depuis I' Antiquite en medecine traditionnelle et pour Ia conservation des aliments fournissent un grand nombre de composes qui possedent des activites antifongiques et antimicrobiennes (Cowan, 1999 Le Myrte (Myrtus communis L.) est un arbuste a feuilles persistantes appartenant a Ia famille des Myrtaceae.…”
Section: Introductionunclassified
“…Laptadaenia pyrotechnica and Sarcostema acidium [31]. Other Asclepiadaceae family members that contain antibacterial activity established successfully include Decalepis hamiltonii [32] H. indicus [33 and 34], Gymnema sylvestrae [35] and Oxystelma esculentum [36].…”
Section: Resultsmentioning
confidence: 99%